Effect of fire on pools of mercury in forest soil, Central Europe - Navrátil, Tomás; Hojdová, Maria; Rohovec, Jan; Penízek, Vít; Varilová, Zuzana (Bulletin of environmental contamination and toxicology, 2009)
In year 2006, 17.9 ha of forest was burned during a forest fire at the Bohemian Switzerland National Park found in northern part of Czech Republic (CR), central Europe. Complete combustion of organic soil (4,039 t) on the burned area caused volatilization of 1.34 +/- 0.07 kg of Hg. Thus Hg emissions due to fire amounted to 75.1 g ha(-1). The average burned forested areas in CR for the period 2000-2006 were reported at 356 ha with estimated Hg emissions at 26.7 kg year(-1), while the average anthropogenic emissions in the same period amounted to 3 t year(-1). Thus estimated mean emissions of Hg from burned forest soil in the period 2000-2006 reached 1% of the annual anthropogenic Hg emissions.
Keywords: Soil Pollutants; Česká republika; rtuť; požáry; stromy; Czech Republic; Trees; volatilizace; Mercury; látky znečišťující půdu; Environmental Pollution; půda; Fires; znečištění životního prostředí; Volatilization; Soil